Selection of hybrid applicators for adaptive cervical cancer brachytherapy: A practical guide - Kilar, Cody; Bajwa, Harjot Kaur; Pifer, Phillip; Beriwal, Sushil (Journal of Contemporary Brachytherapy, 2025)
Image-based adaptive brachytherapy (IGABT) is now the standard of care for patients with locally advanced cervical cancer. EMBRACE-2 MRI-based brachytherapy study demonstrated improved local control rates and reduced morbidity using hybrid applicators. Utilization of these hybrid applicators in gynecological brachytherapy offers advantages over conventional interstitial techniques; however, practical guidance for applicator selection based on disease extent and image findings remains limited. This manuscript aimed to provide a practical framework for applicator selection based on five case scenarios to demonstrate optimal applicator selection tailored to disease extent and anatomical considerations.